“THE POWER OF THE AUTHOR OF NATURE”: AN EXPLORATION OF JOHN WOODWARD’S FUSION OF NATURAL AND REVEALED RELIGION - Bugler, Christine (My University, 2012)
Sir Isaac Newton’s famous discovery of gravity marks the rapid advancement of science in the English seventeenth century, and a permanent shift away from the scientific methods of antiquity. Natural philosophers were beginning to look at the physical world in new and dynamic ways. However, much of this new theory conflicted with traditional theology, which was problematic for Christian followers of this ‘new science’. To negotiate this conflict, a group of natural philosophers developed a new branch of science entitled physico-theology. This stream aims to prove that science does not dismiss religion, but is able to reinforce the existence of God and the truth of Biblical texts. John Woodward is a largely overlooked participant in physico-theology, but his literary works supply key information to modern readers in the understanding of this field. This study critically examines Woodward’s Natural History of the Earth for its significant contributions to early modern science and literary techniques of this discipline. This work is indicative of an emerging scientific method that aims to accommodate both physical observation and creative thinking. I argue that Woodward’s reliance on theology, while scientifically problematic, does not hinder his research, but is perversely productive by challenging him to pursue innovative hypotheses. This prominent, understudied text is remarkable for its fusion of science and theology, and for what it can illuminate about the interdependence of faith and reason in early modern science.
Keywords: John Woodward; early modern science; physico-theology; Natural History of the Earth; Universal Deluge; Biology; Christianity; Literature in English, British Isles; Other Life Sciences; Religious Thought, Theology and Philosophy of Religion; Biology